Effect of Milk Drinking on the Level of Liver Enzymes among Workers of Paint Manufacturing Industry - MA Vahdani manesh; V Abolhasannejad; N Moasheri; D Ketabi (طب کار)
Abstract Background: Aromatic solvents widely have a wide range of usage in various industries. A great number of epidemiologic studies show the liver toxicity resulting from exposing to organic solvents and their effect on liver transaminases. In the present study, the effect of milk drinking on the level of liver enzymes among a paint manufacturing industry workers is evaluated. Methods: The present study is a before & after clinical trial. 162 paint manufacturing industry workers were studied. They had been chronically exposed to aromatic solvents such as Benzene, Toluene and Xylene. Demographic information was collected by using a questionnaire and the level of liver enzymes ALT and AST was measured by blood testing among the studied workers. Feeding workers with 200 ml milk daily was considered as the initial intervening factor, and after one year, again the level of liver enzymes was measured. Results: Mean age of the subjects was 31.5 ± 8.84 year and the mean of body mass index was 24 ± 3.04 Kg/m2. Measuring the concentration of aromatic organic solvents at paint manufacturing hall indicated that, the workers were exposed to these solvents at more than permissible levels. The level of liver enzymes of the studied workers after one year drinking 200 ml milk daily was significantly reduced (P<0.001). Conclusion: Considering that milk drinking was effective in reducing the level of liver enzymes among workers among workers who were chronically exposed to aromatic solvents, therefore, the present intervention can have a major role in preventing the incidence or in reducing the liver lesions among workers predisposed to risk.